Investigating the Impact of the TUITEK® Patient Support Programme, Designed to Support Caregivers of Children Prescribed Recombinant Human Growth Hormone Treatment in Taiwan - Su, Pen-Hua; Malik, Sumaira; Jheeta, Amrit; Lin, Yen-Fan; Su, Su-Huei; Koledova, Ekaterina; Graham, Selina (Frontiers in Endocrinology, 2022)
Purpose Poor adherence to recombinant human growth hormone (r-hGH) treatment presents a significant barrier to achieving optimal growth outcomes. It is important to identify and address the treatment adherence-related needs of children prescribed r-hGH treatment, and develop new approaches to improve adherence. We aimed to measure the impact of the TUITEK® patient support programme, a multi-component personalized service intervention, on caregivers’ knowledge, beliefs, and perceptions of short stature and adherence to its treatment. Patients and Methods The evaluation of the TUITEK® patient support programme was conducted among 31 caregivers of children with short stature and receiving r-hGH treatment via the easypod™ auto-injector device in Taiwan. Caregivers within the ‘high risk’ category for knowledge, beliefs and perception factors influencing adherence to r-hGH treatment (disease and treatment coherence, emotional burden, self-administration, and treatment-related anxiety) were identified via the TUITEK® personalization questionnaire and followed up with bi-weekly telephone calls by a nurse practitioner over a 3-month period. A Wilcoxon signed-rank test was used to compare changes in questionnaire-based scoring patterns between baseline and follow-up. Results Between baseline and follow-up, the percentage of caregivers scoring as ‘high risk’ for emotional burden reduced by 37%; there was an improvement in confidence of self-administration by 57% and the percentage of caregivers scoring as ‘high risk’ for treatment-related anxiety reduced by 52%. At follow-up, all caregivers classified as ‘high risk’ within the disease and treatment coherence item at baseline moved into the ‘low risk’ category. Statistically significant changes in questionnaire scores between baseline and follow-up for disease and treatment understanding, emotional burden, self-administration, and treatment-related anxiety were also observed. Conclusion These findings indicate that the TUITEK® patient support programme can positively address disease and treatment-related barriers amongst caregivers regarding optimal adherence of their children to r-hGH treatment, which has the potential to positively impact on adherence levels and patient clinical health outcomes.